An Overview of the Evidence and Mechanisms of Herb–Drug Interactions - Rosenkranz, Bernd; Fasinu, Pius; Bouic, Patrick (Frontiers in Pharmacology, 2012)
Despite the lack of sufficient information on the safety of herbal products, their use as alternative and/or complimentary medicine is globally popular. There is also increasing interest in medicinal herbs as precursor of pharmacological actives. Of serious concern is their concurrent consumption with conventional drugs. Herb-drug interaction (HDI) is the single most important clinical consequences of this practice. Using a structured assessment procedure, the evidence of HDI presents with varying degree of clinical significance. While the potential for HDI for a number of herbal products is inferred from non-human studies, certain HDIs are well established through human studies and documented case reports. Various mechanisms of pharmacokinetic HDI have been identified and include the alteration in the gastrointestinal functions with consequent effects on drug absorption; induction and inhibition of metabolic enzymes; the induction and inhibition of transport proteins and stimulation of changes to hepatic and renal functions leading to alteration in drug elimination profiles. Due to the intrinsic pharmacologic properties of phytochemicals, pharmacodynamic HDIs are also known to occur. The effects could be synergistic, additive and/or antagonistic. Poor reporting on the part of patients and inability to promptly identify HDI by health providers are identified as major factors in compiling clinically relevant HDIs. A general overview and the significance of pharmacokinetic and pharmacodynamic HDI are provided, detailing basic mechanism and nature of evidence available. The potential of new chemical entities to be involved in HDIs should be considered in their non-clinical safety assessment during the drug development process. More clinically relevant research is also required in this area as current information on HDI is insufficient for clinical applications to increase the level of awareness among health professionals.